Budgetary impact of emicizumab versus activated prothrombin complex concentrate (aPCC) for the prophylactic treatment of hemophilia A with inhibitors - Dongo , Víctor (2023)
Objective: to analyze the budgetary impact of emicizumab compared to activated prothrombin complex concentrate (aPCC) for the prophylactic treatment of hemophilia A with inhibitors. Material and methods: A budget impact analysis in a hypothetical cohort of 26 Peruvian patients with Hemophilia A with inhibitors. The data comes from scientific articles published in peer-reviewed journals. Three scenarios were considered: the e calculated without bleeding episode costs, the price calculated with bleeding episodes treated with aPCC, and the price calculated with bleeding episodes treated with rFVIIa. Results: The savings for using emicizumab range from S/. 67,531,645 to S/. 120,176,763.84, the most likely being S/. 111,008,056.32. In the most conservative scenario, which assumes that the prophylactic use of emicizumab and aPCC have the same risk of annual bleeding episodes, prophylaxis for two years with emicizumab would mean savings of S/.111,008,056.32 or S/ 67,531,645.4 when compared with the prophylactic use of aPCC at doses of 100 IU/Kg or 70 IU/kg every other day, respectively. The scenario that presents the greatest savings is the one assuming that emicizumab reduces the risk of annual bleeding episodes more than aPCC, and both use rFVIIa for the treatment of bleeding episodes. In this scenario, savings could be S/.120,176,763.84 or S /.76,700,352.96 when compared with the prophylactic use of aPCC at doses of 100 IU/Kg or 70 IU/kg every other day, respectively. Conclusions: Emicizumab has a lower financial impact than aPCC.